Angiotensin II, Aldosterone, and Anti-Inflammatory Lymphocytes: Interplay and Therapeutic Opportunities. (21st May 2012) - Kasal, Daniel Arthur B.; Schiffrin, Ernesto L.
Abstract : Inflammation is recognized as an important factor in the pathophysiology of hypertension, with the renin-angiotensin-aldosterone system (RAAS) playing a key role in the disease. Initially described because of its contribution to extracellular fluid and electrolyte homeostasis, the RAAS has been implicated in endothelial dysfunction, vascular remodeling, oxidative stress, proinflammatory cytokine production, and adhesion molecule synthesis by the vascular wall. Both angiotensin II and aldosterone are involved in these systemic effects, activating innate and adaptive immune responses. This paper highlights some aspects connecting RAAS to the hypertensive phenotype, based on experimental and clinical studies, with emphasis on new findings regarding the contribution of an increasingly studied population of T lymphocytes: the T-regulatory lymphocytes. These cells can suppress inflammation and may exert beneficial vascular effects in animal models of hypertension. Erratum to "Angiotensin II, Aldosterone, and Anti-Inflammatory Lymphocytes: Interplay and Therapeutic Opportunities" dx.doi.org/10.1155/2012/132598